Do neighbouring countries encourage the demand of international business tourism? - Carvalho, Pedro (2016)
This paper aims at determining the factors that influence the growth of international business tourism and understanding whether the demand growth of business tourism spreads across neighbouring countries. For the development of the empirical research, data has been collected from a sample of 136 countries worldwide, and spatial econometric techniques have been used. Evidence that supports the idea that the main factors related to the increase in incomes of business tourism are the private investment on tourism assets, the leisure tourism and the trade openness in relation to the outside world is presented. This study also reveals that the demand of business tourism in a country is not contagious, that is, the demand varies neither with the demand of its neighbours nor with their exogenous characteristics. The results have important implications for the choice of tourism policy goals at national levels and the corresponding policy instruments.